Effect of Osmotic Stress on Growth and Water Uptake by Corn Seedlings - Singh, Ramadhar (Journal of Soil and Water Conservation, 2022)
The effects on plant growth of excessive concentrations of soluble salts in the root medium may be mediated by osmotic inhibition of water absorption, by specific effect of the constituent ion or ions in the growth media, or a combination of the two. The qualitative aspect of plant growth on saline media are not without significance in relation to the question of omostic inhibition of growth. Many workers in this field [Eaton (1942). Hayward and Wedleigh (1949)] have noted the progressive stunting of plants and the development of smaller, darker green leaves which in most cases resemble drought symptoms very closely. They support the view that water deficit induced by high osmotic pressure of the growth medium is the factor restricting growth.